Knowledge and Practices on the Treatment of Asthma among Health Workers Working in Level 2 Health Facilities, Bomet County in Kenya - Rob, Joel Kimutai (JOOUST, 2022)
Asthma is a non-communicable disease that affects millions of people globally. However, it is underdiagnosed in sub-Saharan Africa, resulting in outcomes such as deaths. There is an effort by the Kenyan government to provide asthma-related treatment services close to the households. However, health care workers' level of knowledge on the treatment of asthma has not been evaluated. Therefore, a descriptive cross-sectional study on 90 health workers working at level 2 health facilities in Bomet County. The objectives of the study were to: determine the level of knowledge on treatment of asthma among the health workers working in level 2 health facilities in Bomet County; determine practices on the treatment of Asthma among the health care workers in level 2 health facilities in Bomet County and to identify the barriers /challenges on the treatment of Asthma in level 2 health facilities in Bomet County. Data was collected using semi-structured questionnaires and the key informant interview guide. Analysis was done using descriptive statistics by presenting the data in tables using percentages and proportions. This study reports high level of awareness on causes of asthma among health care workers. In addition, the knowledge of the risk factors was excellent, and moderate. However, the inadequate knowledge on treatment was due to a lack of refresher training and approved treatment guidelines. Therefore, this study recommends the provision of the current treatment guideline for asthma and regular re-training of the health care providers on risk factors.